The effect of compulsory schooling on vaccination against COVID and Influenza - Daniel Monsees; Hendrik Schmitz (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
We study the effect of education on vaccination against COVID-19 and influenza in Germany and Europe. Our identification strategy makes use of changes in compulsory schooling laws and allows to estimate local average treatment effects for individuals between 59 and 91 years of age. We find no significant effect of an additional year of schooling on vaccination status in Germany. Pooling data from Europe, we conclude that schooling increases the likelihood to vaccinate against COVID by an economically negligible effect of one percentage point (zero for influenza). However, we find indications that additional schooling increases fear of side effects from COVID vaccination. – – Wir untersuchen die Auswirkungen von Bildung auf die Impfung gegen COVID und Influenza in Deutschland und Europa. Unsere Identifikationsstrategie nutzt Änderungen in Pflichtschulzeiten aus und ermöglicht die Schätzung lokaler Treatmenteffekte für Personen im Alter zwischen 59 und 91 Jahren. Wir finden keinen signifikanten Effekt eines zusätzlichen Jahres an Schulbildung auf den Impfstatus in Deutschland. Für die europäischen Daten, kommen wird zu dem Schluss, dass die Schulbildung die Wahrscheinlichkeit erhöht, sich gegen COVID zu impfen, allerdings nur um einen vernachlässigbaren Effekt von einem Prozentpunkt (Null für Grippe). Wir finden jedoch Hinweise darauf, dass zusätzliche Schulbildung die Angst vor Nebenwirkungen der COVID-Impfung erhöht.
Keywords: I10; 330; COVID; influenza; vaccination; education; compulsory schooling